Electronic structure of the Si(111)3×3R30∘−B surface from theory and photoemission spectroscopy - Aldahhak, Hazem; Hogan, Conor; Lindner, Susi; Appelfeller, Stephan; Eisele, Holger; Schmidt, Wolf Gero; Dähne, Mario; Gerstmann, Uwe; Franz, Martin (Physical Review B)

Dark-state and loss-induced phenomena in the quantum-optical regime of Λ-type three-level systems - Rose, Hendrik; Popolitova, D. V.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Approximate nonlinear wave solutions of the coupled two-component Gross–Pitaevskii equations with spin–orbit interaction - Belobo, Didier Belobo; Meier, Torsten (New Journal of Physics)

Impact of screening and relaxation on weakly coupled two-dimensional heterostructures - Nguyen, T. T. Nhung; Sollfrank, T.; Tegenkamp, C.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Potassium titanyl phosphate Z- and Y-cut surfaces from density-functional theory - Neufeld, Sergej; Bocchini, Adriana; Schmidt, Wolf Gero (Physical Review Materials)

Surface localized phonon modes at the Si(553)-Au nanowire system - Plaickner, Julian; Speiser, Eugen; Braun, Christian; Schmidt, Wolf Gero; Esser, Norbert; Sanna, Simone (Physical Review B)

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

InP and AlInP(001)(2 × 4) Surface Oxidation from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Karmo, Marsel; Runge, Erich; Schmidt, Wolf Gero (ACS Omega)

Lattice parameters and electronic band gap of orthorhombic potassium sodium niobate K0.5Na0.5NbO3 from density-functional theory - Bidaraguppe Ramesh, Nithin; Schmidt, Falko; Schindlmayr, Arno (The European Physical Journal B)
We perform a theoretical analysis of the structural and electronic properties of sodium potassium niobate K1-xNaxNbO3 in the orthorhombic room-temperature phase, based on density-functional theory in combination with the supercell approach. Our results for x=0 and x=0.5 are in very good agreement with experimental measurements and establish that the lattice parameters decrease linearly with increasing Na contents, disproving earlier theoretical studies based on the virtual-crystal approximation that claimed a highly nonlinear behavior with a significant structural distortion and volume reduction in K0.5Na0.5NbO3 compared to both end members of the solid solution. Furthermore, we find that the electronic band gap varies very little between x=0 and x=0.5, reflecting the small changes in the lattice parameters.

Erratum: Efficient implementation of the GW approximation within the all-electron FLAPW method [Phys. Rev. B 81, 125102 (2010)] - Friedrich, Christoph; Blügel, Stefan; Schindlmayr, Arno (Physical Review B)

Bright correlated twin-beam generation and radiation shaping in high-gain parametric down-conversion with anisotropy - Riabinin, M.; Sharapova, Polina; Meier, Torsten (Optics Express)
Uniaxial anisotropy in nonlinear birefringent crystals limits the efficiency of nonlinear optical interactions and breaks the spatial symmetry of light generated in the parametric down-conversion (PDC) process. Therefore, this effect is usually undesirable and must be compensated for. However, high gain may be used to overcome the destructive role of anisotropy in order to generate bright two-mode correlated twin-beams. In this work, we provide a rigorous theoretical description of the spatial properties of bright squeezed light in the presence of strong anisotropy. We investigate a single crystal and a system of two crystals with an air gap (corresponding to a nonlinear SU(1,1) interferometer) and demonstrate the generation of bright correlated twin-beams in such configurations at high gain due to anisotropy. We explore the mode structure of the generated light and show how anisotropy, together with crystal spacing, can be used for radiation shaping.
Keywords: Atomic and Molecular Physics; and Optics

Transient subdiffusion via disordered quantum walks - Geraldi, Andrea; De, Syamsundar; Laneve, Alessandro; Barkhofen, Sonja; Sperling, Jan; Mataloni, Paolo; Silberhorn, Christine (Physical Review Research)

Statistical Benchmarking of Scalable Photonic Quantum Systems - Tiedau, J.; Engelkemeier, M.; Brecht, Benjamin; Sperling, Jan; Silberhorn, Christine (Physical Review Letters)

Experimental entanglement characterization of two-rebit states - Prasannan, Nidhin; De, Syamsundar; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Quantum Correlations beyond Entanglement and Discord - Köhnke, S.; Agudelo, E.; Schünemann, M.; Schlettwein, O.; Vogel, W.; Sperling, Jan; Hage, B. (Physical Review Letters)

Ultrafast electric control of cavity mediated single-photon and photon-pair generation with semiconductor quantum dots - Bauch, David; Heinze, Dirk Florian; Förstner, Jens; Jöns, Klaus; Schumacher, Stefan (Physical Review B)
Employing the ultrafast control of electronic states of a semiconductor quantum dot in a cavity, we introduce an approach to achieve on-demand emission of single photons with almost perfect indistinguishability and photon pairs with near ideal entanglement. Our scheme is based on optical excitation off resonant to a cavity mode followed by ultrafast control of the electronic states using the time-dependent quantum-confined Stark effect, which then allows for cavity-resonant emission. Our theoretical analysis considers cavity-loss mechanisms, the Stark effect, and phonon-induced dephasing, allowing realistic predictions for finite temperatures.
Keywords: tet_topic_qd

Unraveling the electrochemical and spectroscopic properties of neutral and negatively charged perylene tetraethylesters - Wiebeler, Christian; Vollbrecht, Joachim; Neuba, Adam; Kitzerow, Heinz-Siegfried; Schumacher, Stefan (Scientific Reports)
Abstract A detailed investigation of the energy levels of perylene-3,4,9,10-tetracarboxylic tetraethylester as a representative compound for the whole family of perylene esters was performed. It was revealed via electrochemical measurements that one oxidation and two reductions take place. The bandgaps determined via the electrochemical approach are in good agreement with the optical bandgap obtained from the absorption spectra via a Tauc plot. In addition, absorption spectra in dependence of the electrochemical potential were the basis for extensive quantum-chemical calculations of the neutral, monoanionic, and dianionic molecules. For this purpose, calculations based on density functional theory were compared with post-Hartree–Fock methods and the CAM-B3LYP functional proved to be the most reliable choice for the calculation of absorption spectra. Furthermore, spectral features found experimentally could be reproduced with vibronic calculations and allowed to understand their origins. In particular, the two lowest energy absorption bands of the anion are not caused by absorption of two distinct electronic states, which might have been expected from vertical excitation calculations, but both states exhibit a strong vibronic progression resulting in contributions to both bands.
Keywords: Multidisciplinary

Atomically Thin Sheets of Lead‐Free 1D Hybrid Perovskites Feature Tunable White‐Light Emission from Self‐Trapped Excitons - Klement, Philip; Dehnhardt, Natalie; Dong, Chuan-Ding; Dobener, Florian; Bayliff, Samuel; Winkler, Julius; Hofmann, Detlev M.; Klar, Peter J.; Schumacher, Stefan; Chatterjee, Sangam; Heine, Johanna (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Structuring coflowing and counterflowing currents of polariton condensates in concentric ring-shaped and elliptical potentials - Barkhausen, Franziska; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Controlled growth of ordered monolayers of N-heterocyclic carbenes on silicon - Franz, Martin; Chandola, Sandhya; Koy, Maximilian; Zielinski, Robert; Aldahhak, Hazem; Das, Mowpriya; Freitag, Matthias; Gerstmann, Uwe; Liebig, Denise; Hoffmann, Adrian Karl; Rosin, Maximilian; Schmidt, Wolf Gero; et al. (Nature Chemistry)